Early Childhood Caries Is Associated with Genetic Variants in Enamel Formation and Immune Response Genes - (:unkn) unknown (KARGER, 2015)
Early childhood caries (ECC) is a chronic, infectious disease that affects the primary dentition of young children. It is the result of an imbalance of risk factors and protective factors that influence the disease. The aim of this study was to assess genetic and environmental factors that may contribute to ECC. Two hundred and fifty-nine unrelated children were evaluated using a cross-sectional design. Data on oral habits were obtained through a questionnaire, and caries experience data were collected by clinical examination. Twenty-three markers in 10 genes were studied. Genotyping of the selected polymorphisms was carried out by real-time PCR. Regression analyses were performed comparing individuals with and without caries experience. Of 259 subjects, 123 were caries free. The genotype TT in ALOX15 (rs7217186) was a risk factor for ECC, whereas the genotypes GG in ENAM (rs1264848), AG and GG in KLK4 (rs198968), CT in LTF (rs4547741), and GG in TUFT1 (rs3790506) were protective for EEC. In conclusion, environmental factors and gene interactions can act as protective or risk factors for ECC. These factors together contribute to the presence and severity of the disease. (C) 2014 S. Karger AG, Basel.
Keywords: Early childhood caries; Gene-environment interaction; Risk and protective factors; DENTAL-CARIES; MUTANS STREPTOCOCCI; CANDIDA-ALBICANS; EXPERIENCE; POLYMORPHISM; CHILDREN; SCAN